Dominant mutations in a gene encoding a putative protein kinase (BCK1) bypass the requirement for a Saccharomyces cerevisiae protein kinase C homolog. - Lee, K S (1992)
The PKC1 gene of Saccharomyces cerevisiae encodes a homolog of mammalian protein kinase C that is required for yeast cell growth and division. To identify additional components of the pathway in which PKC1 functions, we isolated extragenic suppressors of a pkc1 deletion mutant. All of the suppressor mutations were dominant for suppressor function and defined a single locus, which was designated BCK1 (for bypass of C kinase). A molecular clone of one suppressor allele, BCK1-20, was isolated on a centromere-containing plasmid through its ability to rescue a conditional pkc1 mutant. The BCK1 gene possesses a 4.4-kb uninterrupted open reading frame predicted to encode a 163-kDa protein kinase. The BCK1 gene product is not closely related to any known protein kinase, sharing only 45% amino acid identity with its closest known relative (the STE11-encoded protein kinase) through a region restricted to its putative C-terminal catalytic domain. Deletion of BCK1 resulted in a temperature-sensitive cell lysis defect, which was suppressed by osmotic stabilizing agents. Because pkc1 mutants also display a cell lysis defect, we suggest that PKC1 and BCK1 may normally function within the same pathway. Suppressor alleles of BCK1 differed from the wild-type gene in a region surrounding a potential PKC phosphorylation site immediately upstream of the predicted catalytic domain. This region may serve as a hinge between domains whose interaction is regulated by PKC1.